2017
DOI: 10.5114/aic.2017.70195
|View full text |Cite
|
Sign up to set email alerts
|

Sex-related differences in clinical outcomes and quality of life after transcatheter aortic valve implantation for severe aortic stenosis

Abstract: IntroductionThere are inconsistent data on the sex-related differences in clinical outcomes and quality of life (QoL) after transcatheter aortic valve implantation (TAVI).AimWe sought to investigate sex-related differences in procedural, clinical and QoL outcomes of TAVI.Material and methodsA total of 101 consecutive patients undergoing TAVI were enrolled. Patients were stratified by gender. Baseline characteristics, procedural and long-term clinical outcomes as well as frailty and QoL indices (EQ-5D-3L questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…It could be a potential marker of better mobility and general health status in this group. The evaluation of frailty as well as quality of life [30] have been presented as important factors of overall health status in TAVI patients [10,31]. However, BMI does not enable the discrimination between the components of body or the type and location of fat tissue.…”
Section: Discussionmentioning
confidence: 99%
“…It could be a potential marker of better mobility and general health status in this group. The evaluation of frailty as well as quality of life [30] have been presented as important factors of overall health status in TAVI patients [10,31]. However, BMI does not enable the discrimination between the components of body or the type and location of fat tissue.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, TAVR provides a solution for the substantial proportion of patients who would previously have been untreated despite their poor prognosis. Procedural success with TAVR is comparable between women and men (14,31), but studies have shown that TAVR is associated with a lower risk in terms of 30-day and 1-year mortality in women than in men (1,(7)(8)(9). Furthermore, the TAVR procedure is not associated with any differences in terms of post-procedural frailty or quality-of-life between women and men (14).…”
Section: The Use Of Savr and Tavr For The Treatment Of As In Female Patientsmentioning
confidence: 98%
“…As a result, the majority of relevant differences in sex-specific outcomes are uncovered through post-hoc analyses, calling into question the reliability of the evidence (10). Fortunately, cardiac/valvular device implantation trials in patients with AS do not show gender bias due to a comparable prevalence of disease in male and female patients (13,14). As a result, we sought to determine whether there are significant differences between women and men with regards to the safety and effectiveness of both SAVR and TAVR.…”
Section: Review Articlementioning
confidence: 99%
“…Furthermore, cognitive impairment and depressive symptoms are two risk factors associated with an increased risk of mortality in a progressive, additive manner in elderly adults [ 10 , 11 , 12 ]. Previous research has shown that TAVI improved the health-related quality of life (HRQoL) in multiple dimensions, such as, mobility, self-care, and pain perception, among others [ 13 , 14 , 15 , 16 , 17 , 18 ], and reduced depression and anxiety levels in patients with aortic stenosis [ 19 , 20 ]. The population which benefits from TAVI is increasing.…”
Section: Introductionmentioning
confidence: 99%